Sedimentitas del aptiano tardío al sur de pijao, quebrada la maizena, flanco occidental de la cordillera central, departamento del quindío, colombia (2001)
This work describes the characteristics and geological setting of a fossil-bearing, approximately 45 m thick, pelitic-arenaceous sequence cropping out in the western flank of the Colombian Central Cordillera. The outcrops are located in the middle portion of the La Maizena creek, 8 km in SSW direction of the small Pijao town, located in the southern area of the Quindío Department. The sedimentary sequence occurs in a trending NEE-SSW belt, located east of the "Silvia-Pijao Fault", where the sediments appear in contact with micaceous and amphibolic schists, amphibolites, garnetiferous amphibolites and serpentinized ultramafic rocks, typical of the Arquía Complex, which has been considered by some authors as Paleozoic, by other as Cretaceous in age.  Although the pelites dominate along the studied section, there are also boudin-like bodies of quartzarenites and intercalations of lithic-conglomeratic sandstones as well as thin mafic tuffs. The scarce polarity indicators (normal graded conglomeratic sandstones) indicate that these sedimentary rocks lie in normal position and represent the lower part of a greater succession that passes upward to diabasic flows with sporadic tuffaceous and sedimentary intercalations. This sedimentary sequence seems to have been deposited in an open sea environment, with turbiditic episodes and near to mafic subacuatic volcanic sources. The presence of stable minerals in the sandstones and the occurrence of felsitic and quartzose phyllitic clasts in the lithic portions suggest that these rocks may derive from an eastern pericratonic province.  The fossil content is composed by well preserved ammonites, small bivalves and exclusively planktonic forams. The ammonites (Acanthohoplites all. odiosus ETAYO-SERNA, Phyllopachyceras cf. baborense (COQUAND) and Phyllopachyceras sp.) were collected in the westen portion of the exposed section, and evidence a Late Aptian age. The forams (not described here) were found in a higher level and were dated as Late Aptian-Early Albian age Several thin sections show that the sediments and the diabases have suffered cataclastic deformation, but there are no signs of regional metamorphism. This fact supports previous interpretations considering the Arquía Complex (that includes glaucophane-schists and amphibolitized eclogites) as a precretaceous (Paleozoic) one.